Methods of analysis for functional foods and nutraceuticals - Hurst, W. Jeffrey [ (William Jeffrey)] , 1948- (Functional foods and nutraceuticals series, 2008)
Reflects the advances in the field of functional foods and nutraceuticals. This book provides techniques for the analysis of carotenoids, phytoestrogens, flavonoids, vitamins, and carbohydrates. It contains chapters which discuss peptides, saponins, lignins, and sulfur compounds.